Integrating Gender+ Perspectives in Hydrology Education - Rita Bencivenga; Cinzia Leone; Angela Celeste Taramasso (Engineering Proceedings)
UniGe’s hydrology course emphasises the importance of resilience in overcoming climate challenges. It is in line with the SDGs, integrates considerations of equality, diversity, and inclusion (EDI), and promotes climate resilience and nature-based solutions. This initiative, included in the UniGe Gender Equality Plan (GEP), represents a concrete step towards the inclusion of a gender+ perspective in research and teaching in STEM disciplines, one of the five mandatory GEP areas that the Horizon Europe programme requires from all public research institutions applying for funding. The sustainability and replicability of the initiative at EU level will be discussed.